Analysis of scavenging process in a new two stroke cross - scavenged engine - 261270 Rosli Abu Bakar; Devarajan Ramasamy; Chiew, Chen Wee; International Conference on Advances in Strategic Technologies (3rd. : 2003 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2003)
20